Persepsi Siswa Terhadap Guru Bimbingan Konseling Dalam Pelaksanaan Layanan Bimbingan Kelompok di Smp N 3 Kota Jambi - Yuliyani, Melinda; Rasimin, Rasimin; Lubis , Muhammad Alridho (Jurnal Inovasi Global, 2025)
This research is motivated by the critical role of group guidance services in schools in helping students overcome social, emotional, and academic challenges. The success of these services is greatly influenced by students' perceptions of the guidance and counseling (BK) teachers' skills, particularly in building communication, managing group dynamics, and creating a comfortable and supportive atmosphere. The aim of this study is to describe students' perceptions of BK teachers in implementing group guidance services which focus on four stages of implementation, namely formation, transition, activities, and termination. The method used in this study was descriptive with a quantitative approach. The research sample consisted of 30 seventh-grade students who had participated in group guidance, selected using a sampling technique. Purposive sampling. The results of the study showed that, in general, students' perceptions of guidance counselors were in the good category, with a percentage of 61%. Specifically, student perceptions at the formation stage reached 68%, the transition stage 71%, the core activity stage 69%, and the closing stage 66%, all of which were in the good category. The conclusion of this study shows that the implementation of group guidance services by BK teachers has been quite effective, but there is still a need for quality improvements in the aspects of communication, activity variations, and final reflection to achieve more optimal results.